Biological nitrate transport in sediments on the Peruvian margin mitigates benthic sulfide emissions and drives pelagic N loss during stagnation events. (June 2016) - Dale, A.W.; Sommer, S.; Lomnitz, U.; Bourbonnais, A.; Wallmann, K.
Abstract: Benthic N cycling in the Peruvian oxygen minimum zone (OMZ) was investigated at ten stations along 12 °S from the middle shelf (74 m) to the upper slope (1024 m) using in situ flux measurements, sediment biogeochemistry and modeling. Middle shelf sediments were covered by mats of the filamentous bacteria Thioploca spp. and contained a large 'hidden' pool of nitrate that was not detectable in the porewater. This was attributed to a biological nitrate reservoir stored within the bacteria to oxidize sulfide during 'dissimilatory nitrate reduction to ammonium' (DNRA). The extremely high rates of DNRA on the shelf (15.6 mmol m −2  d −1 of N), determined using an empirical steady-state model, could easily supply all the ammonium requirements for anammox in the water column. The model further showed that denitrification by foraminifera may account for 90% of N2 production at the lower edge of the OMZ. At the time of sampling, dissolved oxygen was below detection limit down to 400 m and the water body overlying the shelf had stagnated, resulting in complete depletion of nitrate and nitrite. A decrease in the biological nitrate pool was observed on the shelf during fieldwork concomitant with a rise in porewater sulfide levels in surface sediments to 2 mM. Using a non-steady state model to simulate this natural anoxia experiment, these observations were shown to be consistent with Thioploca surviving on a dwindling intracellular nitrate reservoir to survive the stagnation period. The model shows that sediments hosting Thioploca are able to maintain high ammonium fluxes for many weeks following stagnation, potentially sustaining pelagic N loss by anammox. In contrast, sulfide emissions remain low, reducing the economic risk to the Peruvian fishery by toxic sulfide plume development. Highlights: Very high rates of dissimilatory nitrate reduction to ammonium by Thioploca. Non-steady state model predicts Thioploca survival on intracellular nitrate reservoir. Ammonium release by Thioploca may be coupled to pelagic N loss by anammox. Thioploca may contribute to anammox long after bottom water nitrate disappearance. Model indicates that benthic foraminifera account for 90% of benthic N2 production.